Characterization of sclerostin’s response within white adipose tissue to an obesogenic diet at rest and in response to acute exercise in male mice - Kurgan, Nigel; Baranowski, Bradley; Stoikos, Joshua; MacNeil, Adam J.; Fajardo, Val A.; MacPherson, Rebecca E. K.; Klentrou, Panagiota (Frontiers in Physiology, 2023)
It is well established that sclerostin antagonizes the anabolic Wnt signalling pathway in bone, however, its physiological role in other tissues remains less clear. This study examined the effect of a high-fat diet (HFD) on sclerostin content and downstream markers of the Wnt signaling pathway (GSK3 and -catenin) within subcutaneous inguinal white adipose tissue (iWAT), and visceral epididymal WAT (eWAT) depots at rest and in response to acute aerobic exercise. Male C57BL/6 mice (n=40, 18 weeks of age) underwent 10 weeks of either a low-fat diet (LFD) or HFD. Within each diet group, mice were assigned to either remain sedentary (SED) or perform 2h of endurance treadmill exercise at 15 m·min-1 with 5° incline (EX), creating 4 groups: LFD+SED (N=10), LFD+EX (N=10), HFD+SED (N=10), and HFD+EX (N=10). Serum and WAT depots were collected 2h post-exercise. Serum sclerostin showed a diet-by-exercise interaction, reflecting HFD+EX mice having higher concentration than HFD-SED (+31%, p=0.03), and LFD mice being unresponsive to exercise. iWAT sclerostin content decreased post-exercise in both 28 kDa (-31%, p=0.04) and 30 kDa bands (-36%, main effect for exercise, p=0.02). iWAT -catenin (+44%, p=0.03) and GSK3 content were higher in HFD mice compared to LFD (+128%, main effect for diet, p=0.005). Monomeric sclerostin content was abolished in eWAT of HFD mice (-96%, main effect for diet, p<0.0001), was only detectable as a 30 kDa band in LFD mice and was unresponsive to exercise. -catenin and GSK3 were both unresponsive to diet and exercise within eWAT. These results characterized sclerostin’s content to WAT depots in response to acute exercise, which appears to be specific to a reduction in iWAT and identified a differential regulation of sclerostin’s form/post-translational modifications depending on diet and WAT depot.